FINANCIAL HEALTH ANALYSIS OF PT GARUDA INDONESIA TBK USING THE ALTMAN Z-SCORE METHOD, FINANCIAL RATIOS, AND CASH FLOW ANALYSIS - Adinda Arum Ariani; Lukmanul Hakim; Oryza Safitri (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to assess the financial health of PT Garuda Indonesia Tbk for the quarterly period of 2023–2025 using three analytical approaches: the Altman Z-Score, financial ratios, and cash flow analysis. This research employs a descriptive quantitative method using secondary data derived from quarterly financial statements. The Altman Z-Score model is applied to measure the level of financial distress, while liquidity, solvency, and activity ratios are used to identify financial conditions from multiple perspectives. Cash flow analysis is conducted to observe the company’s ability to generate cash from operating activities as well as its investment and financing requirements. The results indicate that the Altman Z-Score values of PT Garuda Indonesia Tbk during the study period were mostly within the financial distress zone, although some quarters approached or entered the grey zone. Financial ratios support these findings, showing low liquidity, high solvency pressure caused by significant liabilities and negative equity, and low asset efficiency despite seasonal improvements. Meanwhile, cash flow analysis reveals a positive trend in operating cash flows beginning in mid-2023, indicating that the company’s core activities are recovering. Overall, the financial condition of PT Garuda Indonesia Tbk remains under structural pressure, but demonstrates considerable operational improvement in the medium term.